Le développement durable entre intériorisation de la mondialisation et renouveau territorial, l’exemple lorientais - Florence Gourlay (Territoire en Mouvement)
Sustainable development implies awareness from local communities and the interlinking of planetary environmental, social and economical issues. This particular example thus illustrates a kind of percolating of globalization on a local territorial scale. Territories are now part of a logic of competition and are recomposing. Caught between speeches and actions sustainable development stands today as a framework for thinking and organising planning projects. The greater Lorient had to face brutal, global economical logics and a demand for local development. It tries today to integrate the principles of sustainable development in its approaches toward planning. A new local governance is rising, which among other things tries to improve the active participation of citizens, and reminds us more than ever of the difficulty to think up territorial complexity.